PELAKSANAAN KEGIATAN KEAGAMAAN (BACA TULIS AL-QUR’AN) DI PANTI ASUHAN AL-HIKMA PALEMBANG - Muhammad Sopan; Alimron Alimron; Muhammad Fauzi (PAI RAFAH, 2021)
The problems that will be examined in this research are: First, how is the implementation of religious activities (reading and writing the Qur'an) at the Al-hikma orphanage in Palembang? Second, what are the factors that hinder and support religious activities (read and write the Qur'an ) at the Al-Hikma Orphanage in Palembang? In this study using research. The approach to this research is a qualitative approach with the Field Research method and data collection tools using observation, interviews and documentation. The data analysis uses data reduction, data presentation, and drawing conclusions. The data validity test used participation extension, observation persistence and triangulation. The results of this study are the implementation of religious activities (Read and Write Al-Qur'an) at the Al-Hikmah Orphanage which is carried out 5 times a week. In this activity students not only learn to recite the iqro 'and Al-Qur'an but also learn to memorize Juz Amma and learn to write. Religious activities (Read and Write Al-Qur'an) at the Al-Hikmah Orphanage consists of 2 levels, namely the Al-Qur'an and Iqro 'levels and the methods used are the Qiroati Iqro and recitation methods. The supporting factors for religious activities (Read and Write Al-Qur'an) at the Al-Hikmah Orphanage consist of internal and external factors. Internal factors include motivation in these students. External factors include environmental factors and the condition of the teacher. And the inhibiting factors in religious activities (Read and Write Al-Qur'an) at the Al-Hikmah Orphanage are the lack of intention in students to learn and lack of motivation from within the students.